TerraSAR-X and TanDEM-XRadar Satellites and their Application in Alpine Regions - Eineder, Michael (2010)
Since the year 1991 imaging radar systems are continuously operated on satellites for monitoring the Earth. They work reliably at day and night and even at cloudy or rainy conditions. Therefore they are powerful tools to monitor important environmental parameters such as wind and waves on oceans, sea ice drift, arctic ice sheets or the large forests of the Earth. The resolution of the established radar systems (e.g. ERS-1/2, ENVISAT/ASAR) is on the order of 25 meters which is well suited for global applications but of limited use when it comes to regional monitoring, for example of alpine valleys. In the year 2007 Germany launched TerraSAR-X, the first instance of a new generation of SAR satellites for high resolution monitoring and mapping. The image raster of 1-3 meters, the X-band wavelength and the revisit cycle of 11 days are now much better suited to regional applications. The TerraSAR-X mission is carried out under what is known as a public-private partnership between the German Federal Ministry of Education and Research (Bundesministerium für Bildung und Forschung; BMBF), the German Aerospace Center (Deutsches Zentrum für Luft- und Raumfahrt; DLR) and Astrium GmbH. DLR. The operation of TerraSAR-X is a success story since its launch and a great number of application examples have been demonstrated since. Application areas with high relevance for alpine regions are: - measurement of mountain topography and its changes - measurement of glacier extent and glacier motion vector field - meassurement of tectonic changes - detection of larger landslides - measurement of creeping landslides with millimetric accuracy - structural monitoring of larger infrastructure such as bridges, dams and buildings Focusing on the above topics, the talk summarizes what satellite radar can accomplish today and outlines what could be done specifically for alpine regions in the future.